Data mining techniques and its effect in customer relationship management. (2015) - Singh, Archana; Rana, Ajay; Ranjan, Jayanthi
Data mining technology helps in extracting hidden knowledge from the data. It has been researched extensively over a considerable time period. In this paper, the authors look at developments in the area of data mining for the years 2007 to 2012, focusing mainly on customer relationship management, association rule mining, data mining algorithms and application areas relating to data mining. Data mining offers a wide range of tools and techniques which are used across all sectors of business and industry. This paper refers to a number of sources, including online data, international journal articles, conference proceedings, white papers, books and abstracts. Of the 861 research papers reviewed, around 83 are referenced in this paper. The articles listed here are having relevance with a research domain timeline with their purpose. This review is intended to provide a base framework for academics, customer-centric corporate entities and researchers who use data mining techniques and tools.